East surgical ward enteric perforation score: a new statistically valid scoring criteria for decision between repair or ileostomy in patients with peritonitis due to enteric perforation - Ammar, Ahmed Siddique; Naqi, Syed Asghar; Sattar, Zahra; Inayat, Farwa; Liaquat, Affifa; Janjua, Azwa Munim (International Surgery Journal, 2021)
Background: Enteric fever leading to enteric perforation is very common surgical emergency in the developing nations. The two surgical solutions used worldwide are to repair or exteriorize the perforation as ileostomy. The aim of the study was to setup and validate a statistically reliable scoring system for decision between repair and ileostomy in patients with peritonitis due to enteric perforation. Methods: It was an observational cross-sectional study done at East Surgical Ward of Mayo Hospital, Lahore. 256 patients were selected by consecutive non-probability sampling after ethical approval. The duration of study was 2 years from 1st August to 2018 to 30th July 2020. Patients with age more than 13 years presented in emergency department with diagnosis of peritonitis due to enteric perforation were included. A preformed scoring criterion named as East surgical ward enteric perforation (ESWEP) score was set by giving each variable a score of 1 to 3. Cut-off value between repair and ileostomy was observed. Results: 142 (55.4%) patients were male and 114 (44.5%) were female. Male to female ratio was 1: 1.24. The average age of patients is about 37 years with SD of ±9.67 years. ROC curve showed cut-off of pre-operative ESWEP score of 4 (sensitivity78%, specificity of 88%), per operative score of 7 (sensitivity 96%, specificity of 85%) and total ESWEP score of 11 (sensitivity 94%, specificity of 88%). Conclusions: ESWEP score is new score which helps in standardization of operative procedure done for the patients with peritonitis due to enteric perforation.